Hukum Islam dan Penggunaan Teknologi Informasi di Indonesia - Muhammad Gazali Rahman; Limyah Alamri; Ardin Bataweya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2020)
This paper discusses the relationship between Islamic law and the use of information technology, especially in Indonesia. This research is a library research with the data source in the form of documentation. The results showed that information disclosure in society was due to the development of sophistication in information technology. Everything that happens in other parts of the world in seconds can be known by humans in other parts of the world. Technology was created to serve and facilitate humans in carrying out their life activities. The use of the right information technology can have a positive impact, but the use of inappropriate information technology can have a negative impact. Historical facts in the Islamic world are known to the openness of Muslims to all information in developing Islamic intellectual treasures. In the teachings of Islam, it is found that Allah's affirmation through QS al-Hujurāt/49 verse 12 against facing advances in information technology. Information technology cannot be separated in the development of Islamic law because it can be a tool or media in researching and analyzing a law and developing legal information for the wider community.